Dissenting in the First World War: Henri Bourassa and Transnational Resistance to War - Keelan, Geoff (Cahiers d'histoire)

(untitled) (Cahiers d'histoire, 2018)
This article discusses the connection between French Canadian nationalist, the journalist Henri Bourassa, and other international voices that opposed the First World War. It examines common ideas found in Bourassa’s writing and the writing of the Union of Democratic Control in Britain and the position of Pope Benedict XV about the war’s consequences, militarism and the international system. This article argues that Bourassa’s role as a Canadian dissenter must also be understood as part of a larger transnational reaction to the war that communicated similar solutions to the problems presented by the war.